2021
DOI: 10.3389/fpsyt.2021.782913
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Mental Health Status in General Population: A Series Mediation Examination of Psychological Distress in COVID-19 Pandemic and Global Sleep Quality

Abstract: Background: Coronavirus-2019 (COVID-19) has been coexisting with humans for almost 2 years, consistently impacting people's daily life, medical environment, and mental health. This study aimed to test the series mediation model triggered by childhood trauma, in which perceived psychological impact of COVID-19 pandemic and sleep quality mediated the path sequentially and led to adverse mental health outcomes.Methods: A cross-sectional design involving 817 participants were enrolled via WeChat online survey. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although many studies have confirmed that the COVID-19 epidemic affects SI among college students, the impact on SI among Chinese medical students is elusive. COVID-19 is a socially traumatic public health event, especially for individuals who have experienced a traumatic childhood event and are more vulnerable to the effects of COVID-19 [36]. Several studies have found that individuals who experienced adverse childhood events during the COVID-19 pandemic exhibited higher levels of anxiety, depression and PTSD symptoms [37][38][39].In addition, individuals with a history of childhood abuse experienced increased psychological distress and PTSD symptoms during the pandemic, even over and above demographic characteristics and stressors associated with COVID-19 [40].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have confirmed that the COVID-19 epidemic affects SI among college students, the impact on SI among Chinese medical students is elusive. COVID-19 is a socially traumatic public health event, especially for individuals who have experienced a traumatic childhood event and are more vulnerable to the effects of COVID-19 [36]. Several studies have found that individuals who experienced adverse childhood events during the COVID-19 pandemic exhibited higher levels of anxiety, depression and PTSD symptoms [37][38][39].In addition, individuals with a history of childhood abuse experienced increased psychological distress and PTSD symptoms during the pandemic, even over and above demographic characteristics and stressors associated with COVID-19 [40].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood trauma has been identified as a significant risk factor for developing mental health disorders later in life and has been associated with increased vulnerability to the negative impacts of stress and adversity (27). Previous studies have indicated that childhood trauma plays a role in the development of an unfavorable mental state during the COVID-19 pandemic (28,29). Trauma at an early age can cause an over-activation of the hypothalamus, releasing corticotropin-releasing hormone (CRF), which would lead to an increase in stress hormones such as cortisol and adrenaline (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Combined with strict social distancing rules in many countries around the world, these multiple stressors have had tremendous impacts on mental health and sleep. [4][5][6] Surveys conducted in several countries since the beginning of the pandemic, have reported an increased risk of post-traumatic stress disorder, fear, anxiety, and depression in different populations. [7][8][9][10][11][12] Sleep problems in response to the COVID-19 pandemic are high in prevalence, 13,14 as are psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%